The Lord of the Spear: New iconographic and contextual analysis of a parietal image in an architectural cave at Calakmul - Daniel Salazar Lama; Ana García Barrios.; Benjamín Esqueda Lazo De La Vega (IdeAs)
This article presents a new analysis of an image depicted on one of the two architectural caves of Substructure II C at Calakmul, Campeche, Mexico. The analysis is part of a larger study that seeks to gain a comprehensive understanding of this substructure. Until now, it has been assumed that the figure represented in the image corresponds to a warrior holding a spear. However, a new study allows us to propose an alternative interpretation that associates this individual with a cultural hero of the Maya creation narratives, Juun Ajaw. Our analysis begins with a detailed iconographic examination, after which we contextualise the image and attempt to relate the figure to the architectural environment and the sculptural programme of Substructure II C.